Mechanics of thrust belts and the weak-fault/strong-crust problem - Suppe, J.; Huang, M-H.; Carena, S. (TRABAJOS DE GEOLOGÍA, 2009)
The mechanics of thrust belts and accretionary wedges ultimately concerns the strength of the basal detachment relative to the internal strength of the overlying deforming wedge. We show that detachments are typically very weak absolutely (μ ≤ 0.1 or στ ≤ 0.1 ρgz) and an order of magnitude weaker than the overlying wedge (σ1 ≈ 1.5 to 2 ρgz), which itself may contain weak thrust ramps. A variety of non-classical mechanisms, including those activated in large earthquakes, may control the strengths of major faults in thrust belts. A likely locus of wedge strength is at fault bends, where bulk rock of the thrust sheets must continually deform.